Estimates of cancer burden in Lazio. Issue 3 (May 2013) - Rashid, Ivan; Pannozzo, Fabio; Rossi, Silvia; Foschi, Roberto
Aims and background: Since 1983 a population-based cancer registry has been operating in Lazio which provides incidence and survival data and covers the entire Latina province, amounting to 10% of the regional population. The aim of this paper is to provide estimates of the incidence, mortality and prevalence for seven major cancers in the Lazio region for the period 1970—2015. Methods: The estimates were obtained by applying the MIAMOD method, a statistical back-calculation approach to derive incidence and prevalence figures starting from mortality and relative survival data. Survival was modeled on the basis of published data from the Italian cancer registries. Results: In 2012 the most frequent cancer sites were breast, colon-rectum and prostate with 5, 529, 5, 315 and 4, 759 new diagnosed cases, respectively. The cancers with increasing incidence trends were breast cancer, lung cancer and skin melanoma in women, and prostate cancer, colorectal cancer and melanoma in men. The incidence rates of uterine cervix and stomach cancer decreased. The male lung cancer rates increased, reaching a peak in the late 1980s, and then decreased. Prevalence increased for all the considered cancers except cervix cancer. In 2012 breast, colorectal and prostate cancer had the highest prevalence, with 68, 239, 36, 617 and 33, 934 prevalent cases, respectively. In the final period of the study the mortality declined for all cancers except female lung cancer. In 2012, the highest mortality rates were estimated for lung cancer in both men and women, with 89 and 40 deaths per 100, 000, respectively. Conclusion: These estimates give a useful description of the present and future cancer patterns in the Lazio region. Incidence, mortality and prevalence projections provide new information for health resource planning. Furthermore, they point to the need to reinforce the organized screening programs, especially for breast and colorectal cancer.